Mycobacterium paratuberculosis DNA not detected in Crohn's disease tissue by fluorescent polymerase chain reaction. Issue 5 (November 1995) - Rowbotham, D S; Mapstone, N P; Trejdosiewicz, L K; Howdle, P D; Quirke, P
Abstract : The role of mycobacteria in the aetiology of Crohn's disease has been a contentious subject for many years. Mycobacterium paratuberculosis is known to cause a chronic granulomatous enteritis in animals (Johne's disease) and has been implicated as a possible infectious cause of Crohn's disease. However this fastidious organism is only rarely detected by conventional microbiological techniques. This study used oligonucleotide primers to the species-specific M paratuberculosis IS900 DNA insertion element and the polymerase chain reaction to amplify any M paratuberculosis DNA from intestinal tissue DNA extracts. One oligonucleotide primer was fluorochrome-labelled and the presence of fluorescent amplified product was determined using an automated DNA sequencer with a computerised gel-scanning laser. This method was shown capable of detecting 1-2 mycobacterial genomes. Intestinal tissue samples were obtained from 68 patients with histologically confirmed Crohn's disease, 49 patients with histologically confirmed ulcerative colitis, and 26 non-inflammatory bowel disease controls. In no case was M paratuberculosis detected in any of the inflammatory bowel disease tissue samples and only one non-inflammatory bowel disease case was positive. These results do not support the hypothesis that M paratuberculosis has an aetiological role in Crohn's disease.